2021
DOI: 10.1039/d0ra09347e
|View full text |Cite
|
Sign up to set email alerts
|

A New ternary organometallic Pd(ii)/Fe(iii)/Ru(iii) self-assembly monolayer: the essential ensemble synergistic for improving catalytic activity

Abstract: An ensemble synergistic effect between metals, ligand and support occurs when an electron transferred from GOvia ligand to Ru, and then to Pd or from Fe to Pd, to make Pd more negative, resulting in higher activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…A significant loss in recyclability was not observed after the fourth run; however, a low yield was obtained after the fifth run (51%). When the reaction time was increased to 24 h at the seventh run, an yield of 60% was obtained, suggesting deactivation in the recycling process [27][28][29][30][31][32][33][34]. The contents of Pd and Ni reused at the fourth and fifth runs were also measured, with the values being 1.34 × 10 -7 (fresh: 2.43 × 10 -6 ) mmol/cm 2 and 1.48 × 10 -8 (fresh: 3.38 × 10 -7 ) mmol/cm 2 , respectively.…”
Section: Stability and Recycling Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A significant loss in recyclability was not observed after the fourth run; however, a low yield was obtained after the fifth run (51%). When the reaction time was increased to 24 h at the seventh run, an yield of 60% was obtained, suggesting deactivation in the recycling process [27][28][29][30][31][32][33][34]. The contents of Pd and Ni reused at the fourth and fifth runs were also measured, with the values being 1.34 × 10 -7 (fresh: 2.43 × 10 -6 ) mmol/cm 2 and 1.48 × 10 -8 (fresh: 3.38 × 10 -7 ) mmol/cm 2 , respectively.…”
Section: Stability and Recycling Abilitymentioning
confidence: 99%
“…Studies have demonstrated that the catalytic activity of the mono-or bi-organometallic catalytic monolayers can be improved by quantifying film morphology, tuning the composition of different metals, elucidating the relative distributions of electrons (which are related to the electrical characteristics of the ligand), and modifying the support and synergy of hetero-bimetals [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Appropriate supports, such as silicon with a greater flat surface, can result in a high dispersion and reproducibility of ordered organometallic catalytic monolayers [21-23, 25, 36-38].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of the reported similar studies are presented in Table S5, indicating that a higher TON value of this work could be obtained. Recycling ability is considered an important factorbecause the recycling and stability of catalysts play an important role in industrial applications [13,[28][29][30][31]. As shown in Figure 7, recycling of these catalytic monolayers is also investigated.…”
Section: Figurementioning
confidence: 99%
“…57–62 Previous studies on ligands, the molecular structure of the surface, metal combination, and carrier with the synergy between metals to develop the higher active catalysts have been our effort directions. 14,60–79…”
Section: Introductionmentioning
confidence: 99%